OCT-Angiography Findings in Children with Anisometropic Amblyopia - David Pekica; Nina Košič Knez; Barbara Razboršek; Dušica Pahor (MDPI AG, 2023)
Purpose: The purpose of this prospective study is to show findings of OCT angiography in children with anisometropic amblyopia with a statistically significant difference, regardless of the type of refractive disorder, between the amblyopic and the fellow eye. This research aimed to establish whether there is a difference in vascular density [VD] and size of the foveal avascular zone [FAZ] in the superficial capillary plexus [SCP]. Methods: All children between 9 and 18 years of age who were treated at the Outpatient Clinic for Orthoptics and Pleoptics of the Department of Ophthalmology, University Medical Centre Maribor from January 2020 to December 2022 due to unilateral anisometric amblyopia were enrolled in our study. Fourteen children met the criteria. Cirrus 5000 high-resolution OCT with AngioPlex OCT angiography was used to analyze the size of the FAZ and VD in the SCP and TCS. The paired t-test or Wilcox signed-rank test [p < 0.05] was used for statistical analysis of each parameter between the amblyopic and fellow eye. Results: Mean child age was 13 years ± 2.9 and ranged from 9 to 18 years. Most of the children [85.7%] were boys. The VD of the SCP did not show statistically significant differences between the visually impaired and control eyes [p = 0.328]. The comparison of the FAZ area between the two eyes was also not statistically significant [p < 0.808]. There was also no statistically significant difference in central macular thickness [TCS] [p < 0.291]. Conclusions: Our research results show no statistically significant differences in the VD and the FAZ of the SCP, and in the TCS between the amblyopic and fellow eye in children with unilateral anisometropic amblyopia. Our research did not confirm the results of certain previous studies in which a lower density of the capillary network was present in the visually impaired eye. Further studies with more children are necessary to confirm our results.